Padanan Istilah Rempah Rendang dalam Bahasa Arab: Analisis Terminologi untuk Pembelajaran Bahasa Arab Pariwisata - ABDUL MAJID; MIA NURMALA (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2026)
This study examines the equivalence categories of Rendang spice terms into Arabic, determines the appropriate terminology strategy, and formulates a list of terms for Arabic teaching materials for Tourism Purposes. This is important to do for the need to develop Arabic terminology for specific purposes in the field of culinary tourism, in order to strengthen cultural diplomacy and support effective communication with tourists and connoisseurs of Indonesian culinary specialties originating from the Arab world. This study uses a qualitative approach with a content analysis method focused on the equivalent terms of rendang spice vocabulary and gastronomic analysis to explore the equivalent terms and cultural interpretations in the Arabic context, this study examines 24 spice data sourced from YouTube content @dapurudaawal, Rendang spice term equivalents are collected through the Al Munawwir Indonesian-Arabic dictionary, the Oxford English-Arabic Dictionary, and practical use in digital media both containing rendang recipes and non-recipes containing spice terms in Arabic. The results showed that of the 24 spices analyzed, nine had full equivalence, twelve had partial equivalence, and three had no equivalence. The most appropriate strategies included adopting established terms, functional descriptions for leaf species, and transliteration for endemic plants such as candlenut and masoyi. Furthermore, equivalence recommendations were formulated through gastronomic justification and terminological strategies.